PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KEPUASAN KERJA KARYAWAN TERHADAP KINERJA KARYAWAN PADA KOPERASI SEJAHTERA MOSINDO BERSAMA DI TANGERANG - Rafaeli Gulo; Muhammad Yuda Alhabsyi (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract. This study aims to analyze the influence of Transformational Leadership Style and Job Satisfaction on Employee Performance at Koperasi Sejahtera Mosindo Bersama, Di Tangerang Region, both partially and simultaneously. The research method used is quantitative with a descriptive and causal approach. The population of this study consisted of 54 employees, and the entire population was used as the sample through a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. The results of the multiple linear regression analysis produced the equation Y = -0.086 + 0.324X₁ + 0.632X₂, indicating that Transformational Leadership Style and Job Satisfaction have a positive effect on Employee Performance. The results of the t-test show that Transformational Leadership Style has a positive and significant effect on Employee Performance, with a t-value of 2.456 and a significance value of 0.018 < 0.05. Job Satisfaction also has a positive and significant effect on Employee Performance, with a t-value of 11.013 and a significance value of 0.000 < 0.05. The results of the F-test indicate that Transformational Leadership Style and Job Satisfaction simultaneously have a significant effect on Employee Performance, with an F-value of 1416.771 and a significance value of 0.000 < 0.05. The correlation test results showed a correlation coefficient (R) of 0.991, indicating a very strong and positive relationship between transformational leadership and job satisfaction on employee performance. The coefficient of determination (R²) value of 0.982 indicates that 98.2% of the variation in Employee Performance can be explained by the two independent variables, while the remaining 1.8% is influenced by other variables outside the scope of this study. Keywords: Transformational Leadership, Job Satisfaction, Employee Performance